Giving of Non-Pharmacological Therapy of Young Coconut Water (Cocos Nucifera L.) to Hypertension Patients - Dedi Supriadi; Elis Roslianti; Rizky Perdana Susanto (LPPM STIKes Muhammadiyah Ciamis, 2021)
Hypertension is a condition in which systolic blood pressure is elevated, more than 140 mmHg, and diastolic blood pressure is over 90 mmHg. This disease is also called the “Silent Killer” because it has no distinctive symptoms. Non-pharmacological therapy is a therapy that utilizes natural ingredients. Young coconut water is a non-pharmacological treatment for high blood pressure. Young coconut water contains almost all minerals, and potassium (K) is one of the most abundant ingredients in coconut water. Young coconut water is high in potassium, which helps lower blood pressure. So that young coconut water can be used to treat high blood pressure. The methods used are descriptive and based on a case study approach. The case study was based on a family with high blood pressure problems and ineffective health management. Client and family data collection techniques include the stages of assessment, interviews, observation, physical examination, and documentation research. The results of the case study, when the client's assessment was carried out, complained of inflammation, dizziness, throbbing headaches, and neck stiffness. When checking the client's imperative signs, the client's blood pressure was 170/110 mmHg. Families don't seem to understand how to care for family members with hypertension, and families also don't seem to take advantage of existing health facilities. The established diagnosis is that family health management is not effective. The nursing plan used is non-pharmacological therapy of young coconut water for 3-day visits to reduce the high blood pressure of clients with hypertension. After implementing the action of giving young coconut water (Cocos nucifera) to lower blood pressure in clients with hypertension, it has been found that young coconut water can lower blood pressure, but drinking coconut water was limited by the short study period of 3 days, so the client's blood pressure was always in the normal range of 150/90 mmHg, which is classified as mild hypertension.